Australian musculoskeletal physiotherapist's perceptions, attitudes and opinions towards pre-manipulative screening of the cervical spine prior to manual therapy: Report from the focus groups. (February 2019) - Thomas, Lucy; Allen, Michelle; Shirley, Debra; Rivett, Darren
Abstract: Background: The Australian Physiotherapy Association 2006 VBI Guidelines are used by many of the member organisations of IFOMPT. These Guidelines are due for revision incorporating recent research findings, international guides, and member's recommendations. Purpose: To identify and consider Australian musculoskeletal physiotherapists' recommendations to inform revision of the 2006 VBI Guidelines. Methods: Focus groups were conducted in the five larger Australian state capitals by an independent qualitative researcher and a subject expert. Qualitative data were collected from 41 musculoskeletal physiotherapists who were purposefully recruited for their broad range of experience and qualifications. The five stage Framework Analysis approach was used to analyse and interpret data. Results: Participants recommended that the revised Guidelines have a new title reflecting a broader risk assessment and management approach, encompassing both musculoskeletal and relevant cardio-vascular risks and informed by contemporary research evidence and clinical experience. Participants requested a positively worded stepwise guide to clinical reasoning for all cervical spine manual treatment scenarios including the process of gaining and recording consent. Participants advised on individual components of the Guidelines needing to be revised or removed. The revised Guidelines, once approved, need to be disseminated in written and electronic formats to all clinicians. Training and education are required to ensure appropriate uptake within and beyond the profession. Conclusions and implications: To ensure their clinical acceptance and utility, the Revised Guidelines need to reflect the current use and recommendations of musculoskeletal physiotherapists. Sound knowledge translation processes are then needed to ensure that the Guidelines are incorporated into practice. Highlights: Guidelines represent an important professional standard and medico legal safeguard. Broader scope is needed to increase relevance to all cervical spine management. Revised guidelines should help improve the recognition of serious pathology. Should provide clear guidance on real risk and informed consent requirements, and. Be succinct, easy to read and accessible to all, within and outside the profession.